Simultaneous radar and spaced receiver VHF scintillation observations of ESF irregularities - Tiwari, D.; Engavale, B.; Bhattacharyya, A.; Devasia, C.V.; Pant, T.K.; Sridharan, R. (My University, 2006)
Simultaneous observations of equatorial spread F (ESF) irregularities made on 10 nights during March-April 1998 and 1999, using an 18-MHz radar at Trivandrum (77° E, 8.5° N, dip 0.5° N) and two spaced receivers recording scintillations on a 251-MHz signal at Tirunelveli (77.8° E, 8.7° N, dip 0.4° N), have been used to study the evolution of Equatorial Spread F (ESF) irregularities. Case studies have been carried out on the day-to-day variability in ESF structure and dynamics, as observed by 18-MHz radar, and with spaced receiver measurements of average zonal drift Vo of the 251-MHz radio wave diffraction pattern on the ground, random velocity Vc, which is a measure of random changes in the characteristics of scintillation-producing irregularities, and maximum cross-correlation CI of the spaced receivers signals. Results show that in the initial phase of plasma bubble development, the greater the maximum height of ESF irregularities responsible for the radar backscatter, the greater the decorrelation is of the spaced receiver scintillation signals, indicating greater turbulence. The relationship of the maximum spectral width derived from the radar observations and CI also supports this result.
Keywords: Equatorial ionosphere; Ionospheric irregularities; Plasma waves; VHF scintillation; ESF irregularities; Equatorial spread F